Basic Statistics for the Behavioral Sciences - Heiman Gary W (Houghton Mifflin Company, 1992)
Preface, Getting Started, Introduction, Statistics and the Research Process, Descriptive Statistics: Describing Samples and Populations, Frequency Distributions and Percentiles, Measures of Central Tendency: The Mean and Median and Mode, Measures of Variability: Range and Variance and Standard Deviation, z-Score Transformations and the Normal Curve Model, Describing Relationships, Describing Relationships Using Correlations, Linear Regression and Predicting Variability, Inferential Statistics, Probability: Making Decisions about Change Events, Overview of Statistical Hypothesis Testing: The z-Test, Significance Testing of a Single Sample Mean or a Correlation Coefficient: The t-Test, Significance Testing of Two Sample Means: The t-Test, One Way Analysis of Variance: Testing the Significance of Two or More Sample Means, Two-Way Analysis of Variance: Testing the Means from Two Independent Variables, Nonparametric Procedures for Frequency Data and Raked Data, Appendixes, Gossary, Index.